A review of landscape development and erosion cycles in southern Africa - Corbett, Dudley Harold (Rhodes University, Faculty of Science, Department of Geology, 1979)
The study of landforms has, to a large extent been neglected by exploration geologists. This is surprising because field geology is intimately related with landforms of one type or another. An understanding of the geomorphological history of a particular area will assist in the appreciation of the surficial environment, the processes of weathering, soil formation and duricrust (calcrete , ferricrete silcrete) formation. This has direct application in planning and interpreting geochemical sampling programmes. In order to understand the evolution of landforms it is necessary to study slope development in some detail. Agents of erosion and denudation constantly at work, remove detritus from hillcrests down to the drainage lines which form the local base level from whence material is transported down to the sea. The system is one of dynamic equilibrium, and the concept of grade is important in understanding hillslope evolution. Thus Section (1) of this discussion deals with past and present theories of hillslope evolution. Very little work has been done recently on the geomorphology of Southern Africa and the presently accepted classification of land surfaces is based on the work of Prof. L.C. King (numerous publications). However, through the more recent work of De Swardt and Bennet (1974) on the geomorphology of Natal, it is apparent that the present system of landform classification in Southern Africa requires widespread revision. The relationship of erosion cycles in Southern Africa to the late Jurassic-early Cretaceous break-up of Gondwanaland has received insufficient attention in the past. Erosion cycles bear an intimate relationship to offshore Cretaceous and Tertiary-Recent sedimentation. Valuable information on these sediments has only recently become available as a result of offshore exploration for oil. The findings of De Swardt and Bennet (1974) are summarized in Section (2) and the present land surface classification of Southern Africa is reviewed. Finally, some suggestions on a new interpretation of land surfaces in Southern Africa are given.
Keywords: Landscape changes -- Africa, Southern; Erosion -- Africa, Southern